Academic Writing Competence: a Case Study of Final Year Students - Santi, Chandri Febri; Solvera, Esy (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
Writing is one of the most difficult language skills to master compared to the other four aspects of language skills. In the world of education, especially higher education, academic writing is a writing skill that must be mastered by students. This study aims to describe the academic writing competence of undergraduate students at UIN Sulthan Thaha Saifuddin Jambi and to find out what factors influence student academic writing competence. This research is a qualitative descriptive study. Data collection was carried out by distributing closed questionnaires, document collection, and open interviews. The respondents of this study were 110 final-year students and 10 lecturers in the field of Indonesian science. Research data were analyzed using Miles and Huberman's interactive analysis model which included data reduction, data presentation, and conclusion. The results showed that the academic writing competence of undergraduate students at the final level of UIN Sulthan Saifuddin Jambi was at a good level, with a note that there was a need for improvement in aspects of the content organization such as the ability to describe problems supported by scientific arguments. Two factors affect students' academic writing competence, namely internal and external factors. Internal factors include writing intensity, reading intensity, and self-motivation. While the external factors are academic writing teaching, access to references, and time allocation.